2015
DOI: 10.1097/01.j.pain.0000460333.79127.be
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone rapidly reduces neuropathic pain through astrocyte and nongenomic PPARγ mechanisms

Abstract: Repeated administration of peroxisome proliferator-activated receptor gamma (PPARγ) agonists reduces neuropathic pain-like behavior and associated changes in glial activation in the spinal cord dorsal horn. As PPARγ is a nuclear receptor, sustained changes in gene expression are widely believed to be the mechanism of pain reduction. However, we recently reported that a single intrathecal injection of pioglitazone, a PPARγ agonist, reduced hyperalgesia within 30 minutes, a time frame that is typically less than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 98 publications
1
53
0
9
Order By: Relevance
“…Further studies are needed to investigate the differential effect of pioglitazone on heat and noxious mechanical sensitivity. In addition, we speculate that pioglitazone would reduce cold hypersensitivity as we recently reported that pioglitazone reduced the development of 63 and reversed 30 hyperresponsivitiy to acetone in the spared nerve injury model of neuropathic pain.…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…Further studies are needed to investigate the differential effect of pioglitazone on heat and noxious mechanical sensitivity. In addition, we speculate that pioglitazone would reduce cold hypersensitivity as we recently reported that pioglitazone reduced the development of 63 and reversed 30 hyperresponsivitiy to acetone in the spared nerve injury model of neuropathic pain.…”
Section: Resultsmentioning
confidence: 67%
“…First, spinal sites are rich in PPARγ expression 11, 55, 61 and pioglitazone crosses the blood-brain barrier 56 . Second, intrathecal administration of PPARγ antagonists inhibits the antihyperalgesic effect of both repeated systemic or single intrathecal administration of PPARγ agonists 11, 30, 63 . Alternatively, non-PPARγ mechanisms can be proposed for the antihyperalgesic effects of pioglitazone in PDN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ample evidence supports a role of astrocytes in the development of persistent pain hypersensitivity after injury [41-43]. Inhibition of astrocyte activity has been associated with the antihyperalgesic effect of pioglitazone, a peroxisome proliferator-activated receptor gamma agonist [44]. Direct nerve stimulation induced astroglial activity and cytokine release [45] and prolonged local anesthesia block of afferent neurons delayed the onset of pain-related behavior and reduced nerve injury-induced astrocytic responses [46], indicating that astrocytic response is regulated by neural input.…”
Section: Introductionmentioning
confidence: 99%